PENGARUH INFLASI, PERTUMBUHAN PENDUDUK DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA SEMARANG TAHUN 2011-2020 - Tri zahrotun Wahyuningsih; Salsabila Rahma Anisa; Mufidatul Ulya; Agi Khoerunnisa; M Al Haris (JURNAL SAINTIKA UNPAM, 2022)
The open unemployment rate is someone who wants to work, is trying to get a job but has not managed to get it. The problem of unemployment is a problem that is very difficult to avoid because on average it is experienced in one area, including in the city of Semarang, Central Java. The purpose of this study is to analyze the effect of inflation, population growth and economic growth on the open unemployment rate in Semarang City in 2011-2020. The type of data used is secondary data in the form of time series data for 2011-2020 which is sourced from the Central Statistics Agency of Semarang City. This research method uses the Multiple Linear Regression method. The hypothesis that has a significant effect on the open unemployment rate is inflation. Meanwhile, the coefficient of determination or R-square value of 0.652 means that the variables of inflation, economic growth and population growth are able to explain 65.2% while the remaining 34.8% is explained by other variables.Keywords: Open Unemployment Rate, Multiple Linear Regression, R-Square Value